Health service provider views on measuring patient involvement in healthcare: an interview study with researchers, clinicians, service managers, and policymakers - Bente Skovsby Toft; Trine Ellegaard; Berit Kjærside Nielsen; Camilla Blach Rossen; Jens Thusgaard Hørlück; Mette Spliid Ludvigsen; Hilary Louise Bekker; Lotte Ørneborg Rodkjær (BMC, 2024)
Abstract Background There are several strategies used to assess involvement in their healthcare across service providers. However, there is no consensus on the most appropriate measurement tool to use when evaluating patient involvement initiatives. This qualitative study aimed to explore the perspectives of stakeholders from micro, meso, and macro levels within the Danish healthcare system on measuring patient involvement in their healthcare. Methods This descriptive, explorative study employed semi-structured interviews with open-ended questions to elicit participants' views and experiences of patient involvement and measurement tools. A purposeful sample of participants was identified, to include decision makers, researchers, and health professionals (n = 20) with experiences of measuring patient involvement in healthcare at micro, meso, and macro levels across Danish organizations. Data underwent reflexive thematic analysis. Results Three main themes were identified: 1) Determining the purpose of patient involvement practices and measurement alignment; 2) Reflecting on the qualities, fit, and usefulness of measures; 3) Recognizing conflicting stakeholder paradigms. Despite the interest in and positive attitudes toward patient involvement innovations, views on the meaning and value of evaluating involvement varied; in part, this was attributable to challenges in selecting criteria, methods, and measures for evaluation. Conclusion The findings indicate the need to integrate the perspectives of all key stakeholders in designing the evaluation of patient involvement initiatives. The application of a multiple stakeholder approach and co-production of a multidimensional evaluation may provide some common ground for selecting evaluation criteria and measurement tools in the healthcare setting. Trial registration Danish Data Protection Agency (1-16-02-400-21) 15 October 2021.